Analysis of Hybrid Securing Digital Payment System through Risk Perception - Joe, C. Vijesh (Journal of Electronics and Informatics, 2022)
This study article discusses a novel method of electronic payment wherein a retailer is made incapable of obtaining a customer's payment details which therefore accomplishes a secure transaction. Customers' payment information, often a credit or debit card detail, faces a number of security issues when transmitted to a retailer via the Internet. Credit card data theft, credit card fraud, and data manipulation are all potential threats. A company has the option of either using or storing client information. If a retailer does not take enough precautions to protect its server or system against data thieves, spammers, spyware, malware, and hackers, then their customers' information might be stolen and exploited. The main parts included in this research work are transaction through token issuance and Pedersen commitment approach to provide better efficacy of successfully securing digital payment system. The usual data security requirements are followed by payment gateways, and the most secure techniques and technologies are used when communicating with banks and credit card firms.
Keywords: Mobile payment service; online payment; electronic payment; digital payment security